Intraoperative arterial pressure and delayed cerebral ischemia in patients with aneurysmal subarachnoid hemorrhage after surgical clipping: A retrospective cohort study - Wang, Jie; Li, Runting; Li, Shu; Ma, Tingting; Zhang, Xingyue; Ren, Yue; Chen, Xiaolin; Peng, Yuming (Frontiers in Neuroscience, 2023)
Background Delayed cerebral ischemia (DCI) is a major predictor of poor outcomes in aSAH patients. Previous studies tried to assess the relationship between controlling blood pressure and DCI. However, the management of intraoperative blood pressure in reducing the occurrence of DCI is still inconclusive. Methods All aSAH patients who received general anesthesia for surgical clipping between January 2015 and December 2020 were prospectively reviewed. Whether DCI occurred or not, patients were divided into DCI group or non-DCI group. Intraoperative arterial pressure was measured every minute and recorded in electronic anesthesia recording system along with intraoperative medication and other vital signs. The initial neurological function score, aneurysm characteristics, surgical and anesthetic information and outcomes were compared between the DCI and non-DCI groups. Results Among 534 patients enrolled, a total of 164 (30.71%) experienced DCI. Baseline characteristics of patients were similar between groups. The World Federation of Neurosurgical Societies (WFNS) scale >3, Age>70 years and modified Fisher scale >2 were significantly higher in patients with DCI than not. Though the second derivative of the regression analysis, 105 mmHg was adopted as the threshold for intraoperative hypotension, and did not associated with DCI. Conclusions The threshold 105 mmHg was adopted as intraoperative hypotension though the second derivative of the regression analysis, and could not be proved to associate with delayed cerebral ischemia adjusted by the baseline severity of aSAH and age.